Upaya Peningkatan Nutrisi Pada Pasien Post Sectio Caesarea Di RSU Assalam Gemolong - Anggrahini, Lulia; , Dr. Faizah Betty Rahayuningsih, S.Kep., M.Kes (2016)
Sectio caesarea is a type of delivery by surgery through an incision in the abdominal wall and the uterine wall that aims to deliver the baby. The immediate needs that must be met by mothers with post partum sectio cesarean wound is nutrition. Patients post caesarea changes in the digestive system takes 3 to 4 days of recovery appetite before bowel function returned to normal. Although the levels of estrogen and progesterone decreases after delivery, food intake also decreased 1 to 2 days. This study aims to improve the nutritional status of patients post sectio caesarea. The research was conducted on April 1 to 2 April 2016 at RSU Assalam Gemolong Sragen. The author uses the method of observation or observation, interviews directly from the patient and family, physical examination and use the documentation study by reading the status of the patient's progress during hospitalized. The results showed the mother post sectio caesarea impaired nutrition: nutritional needs less than body requirements due to the pain of surgery and poor nutrition intake. Writer intervention include: assess nutritional status, teach relaxation techniques, suggest that eating small portions but often, give a clean environment, serve the food in warm and attractive packaging, a collaboration with nutritionists, collaboration in pemeberian analgesic. After the intervention carried out for 2 days, the evaluation found nutrients are met. Conclusion of research, the importance of improved nutrition in mothers postpartum caesarea section to perform the activity, metabolism, reserves in the body, accelerate wound healing and the process of milk production.